Evaluating erosion from space: um case study near Uberlândia - Vrieling, Anton; Rodrigues, Silvio Carlos; Sterk, Geert (Sociedade & Natureza, 2005)
Satellites can offer important spatial data for the assessment of soil erosion. This study was conducted to explore how satellite imagery could be used for evaluating erosion in a 10*10 km area in the Brazilian Cerrados. Products obtained from a variety of satellite sensors were analyzed for the purpose of (1) detecting erosion features; and (2) qualitatively mapping erosion risk. Erosion detection was done through visual image interpretation. Optical Terra ASTER images allowed for a better detection and delineation of major gullies as ENVISAT ASAR imagery. Gully dynamics could be assessed by jointly interpreting aerial photos of 1979 and a high-resolution QuickBird image of 2003. QuickBird also allowed for the detection of smaller erosion features, like rills. Erosion risk mapping was performed for the complete study area with a simple qualitative method integrating information on slope and vegetation cover. Slope was calculated from the SRTM DEM, and NDVI, being indicative of vegetation cover, was obtained from a wet-season ASTER image. Both factors were automatically classified based on their relative susceptibility to erosion. The erosion risk map was constructed by combining both classifications with the minimum-operator. The accuracy of the map was good (75 %) when compared to field estimates of erosion risk. The method presented therefore allowed for a quick and proper indication of spatial differences of erosion risk in the study area, particularly concerning rill and sheet erosion.